Investigating the relationship between the quality of electronic services of the intelligent cooperative system on the satisfaction of cooperative companies - safieh siadat; mohammad rezvanmadani; amirhoshang tajfar (تعاون و کشاورزی)
The purpose of this study was to investigate the relationship between the quality of electronic services and the satisfaction of the audience of the Ministry of Cooperatives, Labor and Social Welfare in the Deputy for Cooperative Affairs. The method of this research was descriptive and correlational. The research population was the audience of the intelligent cooperative system, from which 67 people were selected as the sample using the available sampling method. The conceptual model used in this research is Santoz (2003) e-service quality model and Barnes & Vijen customer satisfaction model. In order to collect data, the e-service questionnaire (Mehdinejad and Ghaed Mohammadi, 2016) was used. . Pearson correlation coefficient and regression analysis in SPSS software were used for data analysis. The results of data analysis showed that the relationship between the quality of electronic services of the intelligent cooperative system and customer satisfaction with a coefficient of 0.90 and at a significant level (0,000) is positive and significant and also the results of Pearson correlation of electronic service quality dimensions Availability, completeness, confidentiality and responsiveness) with the satisfaction of the audience with a correlation coefficient between 0,78 Up to 0.87 And at the level of significance (0,000) is positive and significant. Also, the results of regression analysis showed that the quality of electronic services of the intelligent cooperative system up to 0.81 can predict satisfaction changes, which indicates the high dependence of the dependent variable on the independent variable.